Fatigue resistance of the binder jet printed 17-4 precipitation hardened martensitic stainless steel - Radhakrishnan, Jayaraj (2023)
The unnotched fatigue behavior of the 17-4 PH martensitic (α’) stainless steel, additively manufactured using the binder jet printing technique (BJP), with varying porosity levels and in two different aging conditions are investigated and are compared to that of the conventionally manufactured (CM) alloy. As expected, fatigue strength is enhanced by the reduction in porosity, with hot isostatic pressing of the BJP alloy resulting in a fatigue strength that is similar to the CM alloy. Over-aging of the alloy improves its fatigue resistance further, which is caused by an enhancement in the threshold stress intensity factor range for fatigue crack initiation. These variations are rationalized by recourse to the analysis of the microstructure-crack interactions. It was found that the combination of plasticity induced crack closure mechanisms and transformation induced plasticity are dominant at the fatigue crack tip of the over-aged alloy. Fracture mechanics-based Kitagawa and Takahashi diagrams were utilized to illustrate the significance of pore size on the unnotched fatigue resistance of BJP 17-4 PH alloys. These results are discussed in terms of designing alloy fabrication using BJP specifically for cyclic loading conditions.